Pengaruh Penggunaan Gadget Terhadap Motivasi Belajar Anak di Desa Cucum, Kecamatan Kutabaro, Kabupaten Aceh Besar - Karmila Anggraini Porang; Mulhamah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The research objective to be achieved is to determine the impact of the use of gadgets on children's learning motivation. Gadgets as a communication medium are a development from an era that is really needed today, but the impact of excessive use of gadgets can affect children's learning motivation, as evidenced by the results of observations made directly by the author, that most of the children's motivation will fade because it is influenced by gadgets . Children who have been affected by gadgets will be lazy to carry out various thinking or movement activities, because the activity center is within their grasp, in contrast to children who have not or are not affected by gadgets, their learning motivation is higher with various exploratory activities carried out to improve memory and self-creativity.